Gamified Flipped Classroom for Teaching EFL Productive Skills: Exploring Teachers’ Practices and Challenges in an Islamic University - Wardani, Niasisca Agustia; Saefurrohman, Saefurrohman; Balinas, Elvira S. (UIN Salatiga, 2025)
This study explores the implementation of a gamified flipped classroom model by English as a Foreign Language (EFL) teachers at an Islamic university to teach productive skills, specifically speaking and writing. The research aimed to explore the practical application of this model as well as the challenges and opportunities encountered by teachers and students. A qualitative case study design was employed, focusing on a university language enrichment program. Data collection involved preliminary and semi-structured interviews with two EFL teachers and four undergraduate students, in addition to non-participant classroom observations. Thematic analysis, guided by Braun and Clarke’s six-phase framework, was used to analyze the data. The findings indicate that teachers utilized familiar digital platforms, such as WhatsApp and a Learning Management System (LMS), to deliver pre-class flipped content, allowing classroom time to be dedicated to collaborative, gamified activities. This approach fostered student engagement, motivation, and confidence, particularly in group tasks. Despite the presence of challenges such as technological limitations and varied learner readiness, the model effectively transformed teachers into facilitators and created a student-centered environment that supports productive language development. The study concludes that the success of a gamified flipped classroom is dependent on thoughtful planning, accessibility to digital resources, and differentiated instruction. Furthermore, it contributes to the understanding of blended pedagogical models in higher education EFL settings.